O projeto de educação católica em Minas Gerais: as ações de Dom Antônio dos Santos Cabral no cenário educacional de Belo Horizonte, 1922-1956 - Mota, Alessandra Martins (2021)
This dissertation is a document research that aimed to study the actions of Dom Antonio dos Santos Cabral in the educational scenario of Belo Horizonte and, consequently, his role in the project of Minas Gerais Catholic education. The objective was to analyze the historical documents found in the research, understanding the impact of three decades of the episcopal government and its social, political, and educational importance in the Minas Gerais capital. In order to understand the period from 1922 to 1956, in which he was in the administration of the Belo Horizonte Archdiocese, we used as documental sources: the catholic newspapers “O Horizonte” and “O Diário”, the first “Livro de Tombo” of the Archdiocese, several articles from 1943 about the archbishop gathered in the book “Dom Cabral e suas obras”, and other documents from the public collection of Belo Horizonte and the Archdiocese Archive were used as documentary sources. This allowed a better understanding of who Dom Cabral was, how he became an important high clergy of the Brazilian Church and why his modernizing action in defense of the Church's conservative principles became relevant in the Catholic educational destiny of the state, and most importantly, in the initial process of creating the first Catholic University of Minas Gerais.